The CatWalk XT gait analysis is closely correlated with tissue damage after cervical spinal cord injury in rats - Zheng, Guoli; Younsi, Alexander; Scherer, Moritz; Riemann, Lennart; Walter, Johannes; Skutella, Thomas; Unterberg, Andreas; Zweckberger, Klaus (Applied Sciences, 2021)
Objective and consistent assessment of locomotion recovery remains challenging in rodent spinal cord injury (SCI). We, therefore, studied the validity and relevance of the CatWalk XT® gait analysis as a tool for assessing functional outcome in a clinically relevant cervical SCI model in rats. In total, 20 Wistar rats were randomly assigned to either a C6 clip compression/contusion SCI or a sham laminectomy. Locomotion recovery was assessed weekly using the CatWalk XT® gait analysis and the BBB open field score. Six weeks after SCI, the percentage of preserved spinal cord tissue was measured by glial fibrillary acidic protein (GFAP) immunohistochemistry (IHC) staining. Statistical analyses were performed to assess the correlation of the BBB and the percentage of preserved tissue with 30 different CatWalk XT® parameters. SCI caused a bilateral and significant functional impairment in all studied CatWalk XT® parameters. Similar to the BBB, a significant spontaneous recovery could be observed in most of the CatWalk XT® parameters in the following weeks. Correlation between the hindlimb CatWalk XT® parameters and the BBB was good (53% of r values > 0.6) while the correlation between the forelimb and the hindlimb CatWalk XT® parameters and the percentage of preserved tissue was even stronger (83% of r values > 0.6). The CatWalk XT® gait analysis is closely correlated with tissue damage after cervical contusion/compression SCI and can be used as an objective and consistent tool for assessing locomotion recovery.
Gesehen am 16.06.2021